The historical development of zoo elephant survivorship. Issue 2 (8th September 2022) - Scherer, Lara; Bingaman Lackey, Laurie; Clauss, Marcus; Gries, Katrin; Hagan, David; Lawrenz, Arne; Müller, Dennis W. H.; Roller, Marco; Schiffmann, Christian; Oerke, Ann‐Kathrin
Abstract: In the discussion about zoo elephant husbandry, the report of Clubb et al. (2008, Science 322: 1649) that zoo elephants had a "compromised survivorship" compared to certain non‐zoo populations is a grave argument, and was possibly one of the triggers of a large variety of investigations into zoo elephant welfare, and changes in zoo elephant management. A side observation of that report was that whereas survivorship in African elephants ( Loxodonta africana ) improved since 1960, this was not the case in Asian elephants ( Elephas maximus ). We used historical data (based on the Species360 database) to revisit this aspect, including recent developments since 2008. Assessing the North American and European populations from 1910 until today, there were significant improvements of adult (≥10 years) survivorship in both species. For the period from 1960 until today, survivorship improvement was significant for African elephants and close to a significant improvement in Asian elephants; Asian elephants generally had a higher survivorship than Africans. Juvenile (<10 years) survivorship did not change significantly since 1960 and was higher in African elephants, most likely due to the effect of elephant herpes virus on Asian elephants. Current zoo elephant survivorship is higher than some, and lower than some other non‐zoo populations. We discuss that in our view, the shape of the survivorship curve, and its change over time, are more relevant than comparisons with specific populations. Zoo elephant survivorship should be monitored continuously, and the expectation of a continuous trend towards improvement should be met. Abstract : Survivorship of African elephants kept in zoos globally has improved over the decades, covering a range of survivorship patterns reported in different in situ populations. Research highlights: Survivorship of zoo‐managed adult African and Asian elephants has improved over time. Adult survivorship is within the range of historical data for some free‐ranging populations, for some of which survivorship is lower than the current zoo population. Rather than survivorship itself or another measure of "life expectancy" taken from free‐ranging populations, the development of these measures over time should be used as a benchmark.